Effect of Withania Somnifera Root Powder on the Levels of Circulatory Lipid Peroxidation and Liver Marker Enzymes in Chronic Hyperammonemia - B. Harikrishnan; P. Subramanian; S. Subash (E-Journal of Chemistry)
Withania somnifera (L) Dunal (Solanaceae), commonly called Ashwagandha (Sanskrit) is an Ayurvedic Indian medicinal plant, which has been widely used as a home remedy for several ailments. We have investigated the influence of W.somnifera root powder on the levels of circulatory ammonia, urea, lipid peroxidation products such as TBARS (thiobarbituric acid and reactive substances), HP (hydroperoxides) and liver marker enzymes such as AST (aspartate transaminase), ALT (alanine transaminase) and ALP (alkaline phosphatase), for its hepatoprotective effect in ammonium chloride induced hyperammonemia. Ammonium chloride treated rats showed a significant increase in the levels of circulatory ammonia, urea, AST, ALT, ALP, TBARS and HP. These changes were significantly decreased in rats treated with W.somnifera root powder and ammonium chloride. Our results indicate that W.somnifera offers hepatoprotection by influencing the levels of lipid peroxidation products and liver markers in experimental hyperammonemia and this could be due to (i) the presence of alkaloids, withanolids and flavonoids, (ii) normalizing the levels of urea and urea related compounds, (iii) its free radical scavenging property and (iv) its antioxidant property. The exact underlying mechanism is still unclear and further research needed.